The Participation of Legal Community in Crime Prevention Based on Anomie Theory in Batang Batang District (Universitas Terbuka, 2024)
The occurrence of crime or criminal acts in a region is not solely because someone simply wants to commit evil or accidentally commits a crime. Beyond that, the crimes that occur can be related to various elements of community life such as education, population, economy, politics, social, and culture. Every region in Indonesia certainly has different characteristics of these elements, so the tendency and types of crime will vary in each area. This research was conducted to identify the factors contributing to criminality in society, enabling the community to participate in the efforts to combat crime, both through general and specific preventive measures. The method used in this study is Socio-Legal, which examines crime based on the Anomie theory of criminology to help society recognize and prevent crime. Anomie theory correlates anomie with crime rates in society, where, when social rules and values are no longer consistently applied, individuals are more likely to break rules and engage in criminal behavior. This is due to the inability of individuals or society to provide clear recognition and guidance, including the failure of social institutions to implement effective policies in crime prevention. Therefore, based on the perspective of Anomie Theory, further study of crime factors and the active participation of the legal community in crime prevention can be a resolution for the state of anomie.